Pengaruh E-Service Quality Terhadap Online Repurchase Intention dengan E-Trust Sebagai Mediator pada Pengguna Tokopedia (Studi pada Follower Instagram Tokopedia) - listiyana; Rita Alvin; Nur Qomariah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study focuses on the effect of E-service quality effect on online repurchase intention with E-trust as a mediating variable for Tokopedia users. The approach used in this research is explanative quantitative research. The number of respondents from this study amounted to 200 respondents with data collection techniques using google form. Meanwhile, the analysis technique uses multiple linear regression analysis which is then followed by path analysis. The results of this study show that e-trust has succeeded in bridging e-service quality on online repurchase intention, with the level of direct influence > the level of indirect influence, which is 0.418, so it is known that e-service quality has an effect on online repurchase intention through e-trust